Filamentation protects Candida albicans from amphotericin B-induced programmed cell death via a mechanism involving the yeast metacaspase, MCA1 - David J. Laprade; Melissa S. Brown; Morgan L. McCarthy; James J. Ritch; Nicanor Austriaco (Microbial Cell)
The budding yeast Candida albicans is one of the most significant fungal pathogens worldwide. It proliferates in two distinct cell types: blastopores and filaments. Only cells that are able to transform from one cell type into the other are virulent in mouse disease models. Programmed cell death is a controlled form of cell suicide that occurs when C. albicans cells are exposed to fungicidal drugs like amphotericin B and caspofungin, and to other stressful conditions. We now provide evidence that suggests that programmed cell death is cell-type specific in yeast: Filamentous C. albicans cells are more resistant to amphotericin B- and caspofungin-induced programmed cell death than their blastospore counterparts. Finally, our genetic data suggests that this phenomenon is mediated by a protective mechanism involving the yeast metacaspase, MCA1.